2014
DOI: 10.1371/journal.pone.0089128
|View full text |Cite
|
Sign up to set email alerts
|

Male-Specific Association between Dopamine Receptor D4 Gene Methylation and Schizophrenia

Abstract: ObjectiveThe goal of our study was to investigate whether DRD4 gene DNA methylation played an important role in the susceptibility of Han Chinese SCZ.MethodsUsing the bisulphite pyrosequencing technology, DNA methylation levels of 6 CpG dinucleotides in DRD4 CpG island were measured among 30 paranoid SCZ patients, 30 undifferentiated SCZ patients, and 30 age- and gender-matched healthy controls.ResultsStrong correlation was observed among the six CpG sites (r>0.5, P<0.01), thus average methylation levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 36 publications
1
53
2
Order By: Relevance
“…14 Previous studies reported that abnormal gene methylation has a key role in the development of SCZ. 15,16 For the covalent modification of histones, histone acetylation/deacetylation is the primary epigenetic mechanism regulating gene expression, which is catalyzed by two key enzymes, histone acetyltransferase and histone deacetylase (HDAC). 17 HDACs may increase the expression of several key genes in the brain and may also be associated with susceptibility to SCZ.…”
mentioning
confidence: 99%
“…14 Previous studies reported that abnormal gene methylation has a key role in the development of SCZ. 15,16 For the covalent modification of histones, histone acetylation/deacetylation is the primary epigenetic mechanism regulating gene expression, which is catalyzed by two key enzymes, histone acetyltransferase and histone deacetylase (HDAC). 17 HDACs may increase the expression of several key genes in the brain and may also be associated with susceptibility to SCZ.…”
mentioning
confidence: 99%
“…Hypomethylation of genes promoters [77] 98/108 Peripheral blood CpG genome-wide islands Significant differences in DNA methylation at multiple loci [78] 60/30 Peripheral blood DRD4 Hypermethylation in male patients [79] 24/23 2 pairs of discordant twins…”
Section: Articlementioning
confidence: 99%
“…So far, few studies have examined the epigenetic effects of antipsychotics directly in humans and results are far from being clear, as detailed in Table 3 [65,78,82,86]. Patients treated with haloperidol showed a level of global methylation almost normal (control-like), as if the drug may partially rescue global hypomethylation reported in schizophrenia [65].…”
Section: Epigenetics and Pharmacology: Novel Effects Of Old Drugs Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The dopamine receptor D4 gene (DRD4) encodes the D4 subtype of the dopamine receptor, which belongs to the dopaminergic system (18). The alternative methylation of DRD4 is associated with various mental illnesses (19) and a male-specific association between DRD4 methylation and schizophrenia has been identified (20). It has been reported that the DRD4 promoter is hypermethylated in patients addicted to alcohol (21).…”
Section: Introductionmentioning
confidence: 99%